Treatability of Melia composita using vacuum pressure impregnation - Tripathi, Sadhna; Kumar Poonia, Pawan (Maderas. Ciencia y Tecnología, 2025)
The performance of treated wood in the field is ultimately affected by retention and penetration of preservative in wood. In the present study, a new preservative system ZiBOC and a commercially used preservative copper-chrome-arsenate (CCA) were used for evaluation of treatability of Melia composita by the vacuum pressure method at different pressure levels in unsealed and end sealed specimens. The retention and penetration levels of both the preservatives were significantly different at (P< 0.05) in sapwood, heartwood and pith zones. Melia composita exhibited treatability class ‘C’ (21 – 42% penetration). The results revealed that longitudinal penetration in Melia composita was the dominant flow as examined by spot test for copper in unsealed and end sealed specimens.